Survey-Based Competitiveness Assessment of Tourism Transport Enterprises in Uzbekistan - Sobirov, Bobur (Academia Open, 2025)
General Background: Tourism transport enterprises play a crucial role in supporting destination accessibility, visitor mobility, and overall tourism system performance. Specific Background: Evaluating transport enterprise competitiveness requires consideration of multiple operational dimensions, including punctuality, safety, service quality, and route coverage. Knowledge Gap: Existing competitiveness assessment approaches provide limited frameworks that explicitly account for the inverse nature of safety incidents within tourism transport performance evaluation. Aims: This study aims to develop and demonstrate a survey-based competitiveness assessment framework for tourism transport enterprises using benchmark normalization and a weighted integral-index approach. Results: The application of the framework to eight tourism transport enterprises revealed substantial variation in competitiveness scores. Safety performance emerged as a critical determinant of rankings, particularly when incident counts differed significantly among enterprises. The findings also showed that enterprises achieving balanced performance across multiple indicators obtained stronger overall competitiveness scores. Novelty: The study introduces an inverse-normalization treatment for safety indicators within a transparent competitiveness benchmarking framework. Implications: The proposed method provides destination management organizations and transport operators with a practical tool for competitiveness assessment and supports future benchmarking initiatives using larger and more representative datasets. Keywords: Tourism Transport, Enterprise Competitiveness, Safety Performance, Benchmark Normalization, Integral Index Key Findings Highlights Safety records produced substantial differences in enterprise rankings. Balanced operational performance generated stronger composite scores. Route-based comparison procedures were recommended for future applications.